Nanoantioxidants: Pioneer Types, Advantages, Limitations, and Future Insights - Basma Omran (MDPI AG, 2021)
Free radicals are generated as byproducts of normal metabolic processes as well as due to exposure to several environmental pollutants. They are highly reactive species, causing cellular damage and are associated with a plethora of oxidative stress-related diseases and disorders. Antioxidants can control autoxidation by interfering with free radical propagation or inhibiting free radical formation, reducing oxidative stress, improving immune function, and increasing health longevity. Antioxidant functionalized metal nanoparticles, transition metal oxides, and nanocomposites have been identified as potent nanoantioxidants. They can be formulated in monometallic, bimetallic, and multi-metallic combinations via chemical and green synthesis techniques. The intrinsic antioxidant properties of nanomaterials are dependent on their tunable configuration, physico-chemical properties, crystallinity, surface charge, particle size, surface-to-volume ratio, and surface coating. Nanoantioxidants have several advantages over conventional antioxidants, involving increased bioavailability, controlled release, and targeted delivery to the site of action. This review emphasizes the most pioneering types of nanoantioxidants such as nanoceria, silica nanoparticles, polydopamine nanoparticles, and nanocomposite-, polysaccharide-, and protein-based nanoantioxidants. This review overviews the antioxidant potential of biologically synthesized nanomaterials, which have emerged as significant alternatives due to their biocompatibility and high stability. The promising nanoencapsulation nanosystems such as solid lipid nanoparticles, nanostructured lipid carriers, and liposome nanoparticles are highlighted. The advantages, limitations, and future insights of nanoantioxidant applications are discussed.